2015
DOI: 10.1016/j.jpainsymman.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Evidence Suggests That Decrements in Morning and Evening Energy Are Distinct but Related Symptoms

Abstract: Context Little is known about energy levels in oncology patients and their family caregivers (FCs). Objectives This study sought to identify latent classes of participants, based on self-reported energy levels and to evaluate for differences in phenotypic and genotypic characteristics between these classes. Methods Energy subscale scores from the Lee Fatigue Scale were used to determine latent class membership. Morning and evening energy scores were obtained just prior to, during, and for four months follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 78 publications
5
41
6
Order By: Relevance
“…Only one study was found that reported on associations between polymorphisms in cytokine genes and decrements in energy in oncology patients undergoing radiation therapy and their family caregivers. (9) This preliminary evidence provides support for the role of molecular mechanisms involved in inflammatory processes, particularly cytokines, in the etiology of fatigue and decrements in energy in oncology patients.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Only one study was found that reported on associations between polymorphisms in cytokine genes and decrements in energy in oncology patients undergoing radiation therapy and their family caregivers. (9) This preliminary evidence provides support for the role of molecular mechanisms involved in inflammatory processes, particularly cytokines, in the etiology of fatigue and decrements in energy in oncology patients.…”
Section: Introductionmentioning
confidence: 66%
“…(7) In contrast, energy can be defined as an individual’s potential to perform physical and mental activity. (8) As noted in our previous publication,(9) an increasing body of evidence suggests that fatigue and energy are distinct but related constructs. (8, 10, 11) For example, instruments like the Profile of Mood States (POMS)(12) have separate scales for fatigue-inertia and energy-vigor.…”
Section: Introductionmentioning
confidence: 76%
“…Evidence from oncology 3 and HIV 55 patients suggests that decrements in energy levels are a distinct symptom from fatigue. For all four groups of patients in this study, morning and evening energy scores were lower than those reported by patients undergoing RT.…”
Section: Discussionmentioning
confidence: 99%
“…A number of Single Nucleotide Polymorphisms (SNPs) in proinflammatory cytokines have been reported to be linked with breast cancer susceptibility and prognosis [44][45][46][47][48] as well as the development of treatment-related adverse effects [49,50]. Some evidences have emerged from recent literatures that the energy level in an individual may be considered as a distinct but related symptom to fatigue [51][52][53][54]. Therefore, owing to the relationship between fatigue and energy level, it is hypothesized that a significant number of cytokines and neurotransmitters [55][56][57][58] could play a vital role in the development of these related symptoms.…”
Section: Fatigue and Energy Levelsmentioning
confidence: 99%